Economic Burden Of Benign Prostatic Hyperplasia To Patients At The Trust Specialist Hospital In Greater Accra Region - Adu-Gyamfi, D.E. (University of Ghana, 2017)
Background: Benign prostatic hyperplasia (BPH) is one of the most common benign disease of men with about 40% of men aged 50 years and above and 90% aged 80 years and above. During the aging process of men, the prostate grows, often causing troubling symptoms. Even though BPH has been regarded as part of the aging process, the cost of managing the disease in Ghana to patients and family is unclear. Objective: To determine the economic burden of benign prostatic hyperplasia to patients at the Trust Specialist Hospital in Greater Accra Region Methods: A cross sectional descriptive design was adopted for this study. This involved the collection of data from men aged 40 years and above who visited the urology clinic at the Trust Specialist Hospital in Greater Accra Region. A semi structured questionnaire comprising both open and close ended questions was used to collect data from 165 respondents. Standard cost of illness methods were employed in determining the cost incurred by BPH patients. Direct costs were estimated from medical related and non-medical related such as transportation, food and other costs respectively. Indirect cost was estimated by valuing productivity losses to patients due to BPH. Consequences of BPH on patients relative to pain, emotional suffering, discomfort and functional limitation were evaluated using the Likert scale for the description of intangible cost. Results: The total cost of benign prostatic hyperplasia estimated was GHS 114,028.81 (US$ 26,153.40), with direct and indirect cost constituting 99.5% and 0.5% of the total cost. The average monthly cost incurred per patient was estimated as GHS 697.12 (US$ 159.89), accounting for 25.4% of average monthly income of Xl patients. About 78% and 22% of patients had low and moderate intangible cost as a result of BPH. Conclusion: The cost incurred by patients in in relation to the treatment of BPH is high with respect to patients' monthly income. Therefore there is the need for policy and decision makers to consider a policy that enhances early detection of BPH in medical practice to help improve management of BPH and decrease costs.
MPH
Keywords: Ghana; Prostatic Hyperplasia; Trust Specialist; economic burden